Interactive Dashboards and Data Apps with Plotly and Dash : Harness the power of a fully fledged frontend web framework in Python – no JavaScript required /: Harness the power of a fully fledged frontend web framework in Python – no JavaScript required. (2021) - Dabbas, Elias
No abstract available